Funktionsverbgefüge unter Druck: Ein Vorschlag zur Typologisierung verbonominaler Konstruktionen des Deutschen - Fabian Fleißner; Smirnova, Elena (My University, 2025)
Abstract This study investigates German verbo-nominal constructions of the type [auf/unterPP & stehen/stellen/setzen], which have been classified in previous research under the broader phenomenon of “Funktionsverbgefüge” (FVG). While some studies treat FVG as a unified category (von Polenz 1987; Helbig 1979; Kamber 2008), others focus on specific (families of) constructions and their unique properties (Zeschel 2008; Kabatnik 2020; Fleischhauer 2022). This study is a first step toward a typology of German verbal multi-word constructions that dispenses with the assumption of a category of FVG. The aim is to demonstrate that many structures traditionally discussed under this term actually belong to entirely different types of constructions. Consequently, any attempt at overarching categorization proves to be fundamentally flawed. Our analysis concludes that constructions with the pattern [auf/unterPP & stehen/stellen/setzen] can be classified into four distinct groups based on structural and semantic parameters. In none of the identified construction types systematic (= functional) differences can be observed that are attributable to the verbal element when the overall schematic (= constructional) meaning remains constant. We therefore argue that these constructions should not be classified as FVG.